Review of Elli Lemonidou, Ο Α΄ Παγκόσμιος Πόλεμος (1914-1918): Ιστορία μιας οικουμενικής καταστροφής : [The First World War (1914–1918): History of a universal catastrophe] - Theodosiou, Christina (Historein, 2023)
Review of Elli Lemonidou, Ο Α΄ Παγκόσμιος Πόλεμος (1914-1918): Ιστορία μιας οικουμενικής καταστροφής [The First World War (1914–1918): History of a universal catastrophe]. Athens: Estia, 2020. 216 pp.